Limited effects of dominant ants on assemblage species richness in three Amazon forests - Baccaro, Fabricio Beggiato; Souza, Jorge Luiz Pereira; Franklin, E.; Landeiro, Victor Lemes; Magnusson, William Ernest (Ecological Entomology, 2012)
Ants are highly interactive organisms and dominant species are considered to be able to control the species richness of other ants via competitive exclusion. However, depending on the scale studied, inter-specific competition may or may not structure biological assemblages. To date, ant dominance-richness relationships have only been studied in small sample units, where a few dominant colonies could plausibly control most of the sample unit. We conducted a comprehensive survey of terrestrial ant assemblages using bait, pitfall, and litter-sorting methods in three sites in Brazilian Amazonia. Using a spatially structured rarefaction approach, based on sampling units with linear dimensions ranging from 25 to 250 m, the mesoscale patterns of ant dominance-richness relationships (sampling units covering hundreds of meters separated by kilometers) were investigated. Interference-competition models (parabolic or negative linear relationships between species richness and the abundance of dominant ants) tended to be more frequent in smaller sample units or in assemblages sampled with interactive methods, such as baits. Using more inclusive sampling methods, the relationship was generally asymptotic rather than parabolic, with no reduction in species diversity because of the presence of dominants. Random co-occurrence patterns of species within sites support the interpretation of a limited role for present-day competition in structuring these assemblages. Competition from dominant species may reduce species richness in small areas, especially when artificial baits are used, but appears to be less important than environmental constraints in determining ant species richness across scales of hectares and greater in these Amazon forests. Published 2011. This article is a U.S. Government work and is in the public domain in the USA.
Keywords: Ant; Coexistence; Colony Structure; Community Structure; Competition (ecology); Dominance; Interspecific Competition; Linearity; Pitfall Trap; Spatial Analysis; Species Richness; Survey; Tropical Forest; Amazonas; Formicidae